Process of adoption into turkish in veterinary education in turkey - Halis Yeıitkaya; Abdullah Özen (Eurasian Journal of Veterinary Sciences)
Education of Veterinary Medicine at scientific sense in Turkey was staned in 1842 by Godlewsky who came from Prussia. From this date until the end ot 19th century, the appointment of foreign staff for education in the school, the increase in academical and professional contacts at international level within the field of veterinary medicine, and the efforts exerted to reflect the western scientific understanding upon the education caused Turkish to be influenced by foreign languages. Studies on adoption of Turkish as dominant language were started with Tanzimat, 1839 regulations; and the first senous step in this aspect was taken with the Revulation in Turkish alphabet in Republic era. Studies to adopt into Turkish were started on scientific terms; and within the time. Humane and Veterinary Medical fields were affected. Studies to adopt into Turkish in veterinary medicine processed in parallel with those in Medicine, and the progresses in both fields completed each other. Studies to adopt into Turkish in Veterinary Medicine were noticed in basic sciences like Anatomy, and it particularly turned into a systematical format within the structure of Higher Agriculture Institute. Purification and simplification studies on the terms, idioms and words of Humane and Veterinary Medicine at scientific sense has been continued for centuries despite all disadvantages that were confronted at different periods, and it is also continuing at present. The presentation of a new concept into the use of humanity from day to day in parallel to scientific developments in this era. could be considered as the continuation of studies to lind out terms matching these concepts in the future.